Indigenous Peoples’ Concerns for Environment: Examining the Role of Non-Governmental Organizations (Fourth World Journal, 2025)
According to the United Nations, there are around 370 million indigenous peoples found in almost 70 countries across the world (UNPFII, 2006). Indigenous peoples are the ‘original’ inhabitants of their lands, the majority of whom were forcefully removed from their territories by the brutal forces of European colonizers since the early sixteenth century. Because of their original or first occupancy of their lands and territories, these indigenous peoples are also known as ‘first generation’ people and ‘natives’. In contemporary times, indigenous peoples face a number of issues such as discrimination in education and employment, unavailability of health facilities, rampant poverty, and degradation of environment and ill-effects of climate change. Most of these concerns are not addressed by their states. This is the reason that non-governmental organizations (NGOs) have pitched in and tried to deal with these issues faced by indigenous peoples.The present paper aims to analyze the role played by NGOs in highlighting the indigenous peoples’ issues related to the environment at the international level. This is done by examining the multitude of functions carried out by NGOs such as lobbying, advocacy, and networking, through which many of the serious environmental issues faced by indigenous peoples such as degradation of biodiversity, burning of forests on a large scale, and misuse of their traditional knowledge were addressed by NGOs. The paper is broadly divided into two parts: the first part discusses the concept of indigenous peoples in general and explains the relationship they have with their environment. The second part of the paper examines the role of NGOs in international politics in general, and in the environmental issues of indigenous peoples in particular. The paper concludes with the contention that the involvement of NGOs (both local as well as international) has brought positive outcomes for indigenous peoples. However, much needs to be done to incorporate the real indigenous voices at the international level.